Success Factors for exporting firms - Crompton, Brendan (My University, 2011)
This research aimed to investigate successful and unsuccessful exporting firms based in South Africa. Whilst much research has been conducted into exporters from developed countries, there is relatively little material on exporters from developing countries. The findings from this research were compared to the findings of similar research done on Indian exporting firms. This was done to try and ascertain whether or not there are common success factors for exporting firms based in the two different developing countries and to establish if the export success of Indian exporters could provide any guidance to South African exporters. The research was conducted via a series of semi-structured interviews in which the export managers from the participating firms where posed a series of questions set by the researcher. The data from the interviews was analysed and the findings compared with the findings of similar research conducted in India. The research found that the South African firms who partook in the study were more likely to succeed as exporters if they exported to developed (1st world) countries, had export managers who were relatively new in their position and had a larger number of export customers each accounting for a smaller percentage of export sales. The research concurred with one of the findings from previous research on Indian exporters, namely that firms exporting to developed markets were more likely to succeed as exporters. The current research also suggested, as in the research on Indian exporters, that firms operating in more turbulent business environments had a greater chance of success as an exporter.
MBA - WBS
Keywords: Exporters - Developing countries; Exporters - South Africa